1996
DOI: 10.1074/jbc.271.2.907
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Mutant Influenza Virus Hemagglutinins Is Influenced by Cytoplasmic Sequences Independent of Internalization Signals

Abstract: A mutant influenza virus hemagglutinin, HA؉8, having a carboxyl-terminal extension of 8 amino acids that included 4 aromatic residues, was internalized within 2 min of arriving at the cell surface and was degraded quickly by a process that was inhibited by ammonium chloride. Through second-site mutagenesis, the internalization sequence of HA؉8 was found to closely resemble the internalization signals of the transferrin receptor or large mannose 6-phosphate receptor. Comparison of the intracellular traffic of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 61 publications
5
46
0
Order By: Relevance
“…This is in line with former observations (25) on HA-Y543, which demonstrated temperature-dependent dynamic interactions with coated pits. As for HAϩ4, whose internalization is extremely slow (28), this mutant did not show detectable reduction in its lateral mobility, and diffused in the membrane in an unrestricted manner, just like HA wt.…”
Section: The Mode Of Interactions With Coated Pits Depends On the Intmentioning
confidence: 81%
See 3 more Smart Citations
“…This is in line with former observations (25) on HA-Y543, which demonstrated temperature-dependent dynamic interactions with coated pits. As for HAϩ4, whose internalization is extremely slow (28), this mutant did not show detectable reduction in its lateral mobility, and diffused in the membrane in an unrestricted manner, just like HA wt.…”
Section: The Mode Of Interactions With Coated Pits Depends On the Intmentioning
confidence: 81%
“…The mutants are depicted in Table I. The derivation of the mutants HAϩ8 (containing a carboxyl-terminal extension of eight amino acids with four aromatic residues, generating a strong internalization signal), HAϩ4 (which is HAϩ8 minus the last four residues), and HAϩ8-S548,S554 (HAϩ8 with the tyrosines at positions 548 and 554 replaced by serines) is detailed elsewhere (28). HA-Y543, which is a point mutant of HA wt (cysteine 543 replaced by tyrosine), was described previously (9).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that the rate-limiting step for lysosomal targeting is not endocytosis. Further support for this idea comes from studies on mutant hemagglutinins by Zwart et al (54), who demonstrated that targeting to the latter stages of endocytic pathway does not simply correlate with the concentration of mutant hemagglutinins in the early endosome (54). With their hemagglutinin mutants, they demonstrated that there was no correlation between internalization rate and degradation rate and, furthermore, that the signal for these two processes were distinct.…”
Section: Discussionmentioning
confidence: 99%